Hybrid wind and solar charge controller - Muhammad Syarifuddin, Rahmat (2012)
Environmental concern over the use of conventional sources has reached an alarming stage, thus alternatives sources is imminent. Renewable sources such as wind and solar has gain popularity and demand over the last decade. Power produced from these sources depends very much on the weather condition. Thus, combination of these sources had shown excellent potential as complementary option to generate power. This project will investigates the prototype combination of the solar and wind turbine charging system. The voltage generated from the PV and wind turbine will be recorded everyday and then is need to calculate the average power generated. The old data from the past experiment at Universiti Malaysia Pahang, Pekan will be use to make it as reference or comparison with new data. It is expected that new charging system is reliable and able to charge the battery at optimum power.